Unattended compared to traditional blood pressure measurement in patients with rheumatoid arthritis: a randomised cross-over study. (1st January 2021) - Bartoloni, Elena; Angeli, Fabio; Marcucci, Elisa; Perricone, Carlo; Cafaro, Giacomo; Riccini, Clara; Spighi, Lorenzo; Gildoni, Benedetta; Cavallini, Claudio; Verdecchia, Paolo; Gerli, Roberto
Abstract: Background: Hypertension is characterised by a high prevalence, low awareness and poor control among rheumatoid arthritis (RA) patients. Correct blood pressure (BP) measurement is highly important in these subjects. The "unattended" BP measurement aims to reduce the "white-coat effect, " a phenomenon associated with cardiovascular risk. Data on "unattended" BP measurement in RA and its impact on hypertensive organ damage are very limited. Methods: BP was measured in the same patient both traditionally ("attended" BP) and by the "unattended" protocol (3 automated office BP measurements, at 1-min intervals, after 5 min of rest, with patient left alone) by a randomised cross-over design. Patients underwent clinical examination, 12-lead electrocardiography and trans-thoracic echocardiography to evaluate cardiac damage. Results: Sixty-two RA patients (mean age 67 ± 9 years, 87% women) were enrolled. Hypertension was diagnosed in 79% and 66% of patients according to ACC/AHA and ESC/ESH criteria, respectively. Concordance correlation coefficients between the two techniques were 0.55 (95%, CI 0.38–0.68) for systolic BP and 0.73 (95%, CI 0.60–0.82) for diastolic BP. "Unattended" (121.7/68.6 mmHg) was lower than "attended" BP (130.5/72.8 mmHg) for systolic and diastolic BP (both p < .0001). Among the two techniques, only "unattended" systolic BP showed a significant association with left ventricular mass ( r = 0.11; p = .40 for "attended" BP; r = 0.27; p = .036 for unattended BP; difference between slopes: z = 3.92; p = .0001). Conclusions: In RA patients, "unattended" BP is lower than traditional ("attended") BP and more closely associated with LV mass. In these patients, the "unattended" automated BP measurement is a promising tool which requires further evaluation. KEY MESSAGES: "Unattended" automated blood pressure registration, aimed to reduce the "white-coat effect" is lower than "attended" value in rheumatoid arthritis patients. "Unattended" blood pressure is more closely associated with left ventricular mass than "attende" registration.